Statistical analysis of the Fourier Spectra of the ENCODE regulatory regions - Paredes, O.; Romo-Vázquez, R.; Vélez-Pérez, H.; Morales, J. A. (Revista Mexicana de Ingenieria Biomedica, 2017)
Nowadays, new genomic databases (DNA sequences) are available to the whole scientist community for its analysis. The bioinformatics has developed algorithms to extract information and features of the sequences. However, the bioinformatics algorithms have restrictions. An alternative is the use of digital signal processing (DSP) tools adap-ted to genomic sequences (genomic signal processing – GSP). This work analyzes the first four statistics moments (mean, standard deviation, skewness and kurtosis) and other two moments (median and variance) of the frequency spectra of 15 regulatory regions (RRs) in ENCODE database with the main objective of studying the statistics di-fferences and frequency features. The selected database is mapped. Then, the FFT is calculated to these genomic signals and finally the statistic moments implemented. The results show a three-group behavior in the RRs with the mean, median and kurtosis. The deviations standard and the variance do not show important behavior. Finally, the skewness shows a homogeneous behavior with the lack of atypical values in some RRs. These observations support the idea of the presence of periodicities in a sequence that may be related or may determine the biological function that a sequence may perform.